Evaluation Feedback for Effective Learning and Accountability - OECD (OECD, 2001)
Evaluation is a key tool in improving the quality and effectiveness of development co-operation. The Development Assistance Committee (DAC) Working Party in Aid Evaluation is the only international forum where bilateral and multilateral evaluation experts meet regularly. Its Members meet to improve evaluation practice and to learn lessons from development co-operation activities and experiences. A series "Evaluation and Aid Effectiveness" was launched to share selected pieces of work with a broader public. This publication is composed of two parts: The Workshop Report, based on the fore-mentioned meeting, highlights the various issues raised, topics of discussion and different feedback systems, and outlines the areas identified by participants as most relevant for improving evaluation feedback. The Background Synthesis Report, intended as a starting point for discussion at the workshop, outlines the main concerns and challenges facing evaluation feedback and the means to address these. The report is based on an analysis of questionnaire results, and a review of previous initiatives in this area. The print version of the above report is available free of charge from the Development Co-operation Directorate; please send an email to dac.contact@oecd.org to get a copy.
Google-Books-ID: kA39FghYYUgC

The Soul in the Computer: The Story of a Corporate Revolutionary - Waugh, Barbara (Inner Ocean Publishing, 2001)
When Barbara Waugh joined the Hewlett-Packard Corporation in the mid-80's, this 60's radical encountered a company with a benign but topdown leadership. As she progressed from recruiting manager to world change manager, she used a set of radical tools to transform its corporate culture and to help realize the true potential of The HP Way.

Outcome Mapping: Building Learning and Reflection into Development Programs - Earl, Sarah; Carden, Fred; Smutylo, Terry; Patten, Michael Quinn (IDRC Books, 2001)
"Outcome Mapping provides not only a guide to essential evaluation map-making, but also a guide to learning and increased effectiveness, and affirmation that being attentive along the journey is as important as, and critical to, arriving at a destination." - Michael Quinn PattonMore and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. "Outcome Mapping" recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, "Outcome Mapping" debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.